Bubbles, banks and financial stability - Kosuke Aoki; Kalin Nikolov (European Central Bank (ECB), 2012)
We build a model of rational bubbles in a limited commitment economy and show that the impact of the bubble on the real economy crucially depends on who holds the bubble. When banks are the bubble-holders, this amplifies the output boom while the bubble survives but also deepens the recession when the bubble bursts. In contrast, the real impact of bubbles held by ordinary savers is more muted.
Keywords: 330; financial stability